Best use of biomass? Greenhouse gas lifecycle analysis of predicted pyrolysis biochar systems - Hammond, James A. R. (The University of Edinburgh, 2009)
Life cycle analysis is carried out for 11 predicted configurations of pyrolysis biochar systems to determine greenhouse gas balance, using an original spreadsheet model. System parameters reflect deployment in Scotland, and results demonstrate that all major crop and forestry feedstocks offer greater GHG abatement than other bioenergy technologies, regardless of system configuration. Sensitivity analysis determines the relative importance of uncertain variables in the model and optimistic to pessimistic scenarios are used for system operation. Slow pyrolysis is compared to fast pyrolysis and biomass co-firing for GHG abatement and electricity production, using various scenarios for availability of indigenous Scottish feedstocks.
The best use of biomass? Greenhouse gas lifecycle analysis of predicted pyrolysis biochar systems
Keywords: Geoscience; carbon capture; carbon sequestration; MSc Carbon Capture and Storage